CHARAKTERYSTYKA OPADÓW ATMOSFERYCZNYCH W GORZOWIE WIELKOPOLSKIM W LATACH 1951–2016 - SZYGA-PLUTA, KATARZYNA; WOJTKOWIAK, DOMINIKA (Badania Fizjograficzne Seria A - Geografia Fizyczna, 2019)
The purpose of the work is to characterize the precipitation occurrence and the synoptic conditions of the extreme cases in Gorzów Wielkopolski. In the paper the daily precipitation data from IMGW-PIB for Gorzów Wielkopolski station in years 1951–2016 were used. The average monthly, annual and seasonal sums were calculated and the intensity of precipitation was analyzed. Days without any precipitation were also included. Special attention was paid to extreme precipitation cases and their synoptic conditions. The average precipitation in the research period was 547,1 mm. On average, as much as 80% during the year were days with very low (0.1–1.0 mm) and low (1.1–5.0 mm) precipitation, and 13% with moderate (5.1–10.0 mm). Extreme daily precipitation totals in Gorzów Wielkopolski (95th percentile) occur mainly in summer and spring. They are associated with the transition of the atmospheric front or with the development of convection over heated land.